Hometown advantage: the making of a modern suburb. Issue 2 (7th February 2020) - Parsons, Jeremy; Harris, Richard
ABSTRACT: We know remarkably little about how suburbs are developed, especially in mid-sized urban centers. A wide-ranging literature review, historical and contemporary, indicates that developers are key, risk-taking agents, who seek compensation in high profit margins, and that they require local knowledge together with cooperation from local politicians with whom they develop close relations. Anecdotal evidence and plausible speculation suggest that their symbiosis is closest in suburban settings and smaller urban centers, where developers are more likely to be homegrown. A case study of the Meadowlands, a suburban project adjacent to Hamilton, Ontario, confirms these general and more geographically-specific expectations about developers and the development process. It draws on planning documents, newspaper accounts, legal decisions, and interviews with local land developers, politicians, and planners. By comparison with the United States, distinctive Canadian elements are tighter land use regulations and the supervisory role played by the province of Ontario.